Genetic diversity of H’mong short tail dog based on sequencing of the D-loop hypervariable -1 region (HV1) - Hai, Pham Thanh; Phuong, Bui Xuan; Coi, Tran Huu; Tung, Phung Thanh; Duc, Ngo Quang; Khang, Nguyen Minh; Duy, Vu Dinh (Vietnam Journal of Biotechnology, 2021)
The H'mong short tail dog is breed indigenous dogs, distributed in mountainousareas of northern Vietnam. H'mong short tail dog possesses many valuable properties such as intelligence, agility, good health, good shape, human friendliness, ease of training and it can fully meet the needs of war Dogs intelligence, strength, good parenting, people friendly and more importantly, still keeping wild characteristics of hunting dogs. The total 45 samples (blood) collected from 45 individuals in two provinces of Northern Vietnam (Ha Giang and Lao Cai), were used to assess genetic diversity based on sequencing hypervariable – 1 region (HV1) in D-loop genes. In the current study showed that genetic diversity of H'mong short tail dog was high with nucleotide diversity (Pi = 0.00801), haplotype diversity (Hd = 0.96162) and average number of nucleotide differences (Kt = 5.18384). Furthermore, 25 different haplotypes were recorded and divided into four main groups: A, B, C, and E. Of which, seven new haplotypes in haplogroups A (An1 to An7) and 18 haplotypes have been published in the world. In addition, H'mong short tail dog was found rare haplogroups (B1, C2, E1 and E4). Notably, there is none individuals contain haplotype of haplogroups (D and F). H'mong short tail dog were identified 38 single nucleotide polymorphisms, including 32 nucleotide base substitution/base insertion and 6 nucleotide indel mutation. Almost mutation was transversion (31/32) and only one nucleotide transition mutations. Phylogenetic tree shown that H'mong short tail dog have close relationship with dogs origin from East Asia (China, Japan and Korea).